CHANGE OF WORDS César Hildebrandt, Penguin Random House Editorial Group: DEBATE, Third Reprint: September 2018. - Gutiérrez Gómez, Edgar (2020)
The political events of a nation rule the agglomerated milestone of opinion figures, who agitate the masses for a particular political ideology. That representation is subject to politicians representing a political party, at the same time it has to be based on programmatic ideologies with a journalistic dissemination body that points to a rule in its historical process, for example the ideological struggles in the journalistic industries: “The group tends to assimilate all the elements capable of claiming socialism without excepting those that come from gonzalezpradista radicalism and are preserved outside the political parties ”(Mariátegui, 1986, p.99)